The combination of nanotechnology and potassium: applications in agriculture - Qibin Wang; Chen Shan; Peng Zhang; Weichen Zhao; Guikai Zhu; Yi Sun; Quanlong Wang; Yaqi Jiang; Noman Shakoor; Yukui Rui (Environmental Science and Pollution Research, 2023)

Antiviral effects of duck type I and type III interferons against Duck Tembusu virus in vitro and in vivo - Peng Zhou; Dejian Liu; Qingxiang Zhang; Wanrong Wu; Dong Chen; Rui Luo (Veterinary Microbiology, 2023)

Granulation of partial denitrification sludge: Advances in mechanism understanding, technologies development and perspectives - Duanyuan Xu; Shenbin Cao; Maxence Berry; Rui Du; Yongzhen Peng (Science of The Total Environment, 2023)

Hydroxyapatite (HAP) formation in acetate-driven partial denitrification process: Enhancing sludge granulation and phosphorus removal - Yu Lan; Xing Li; Rui Du; Xiaoyan Fan; Shenbin Cao; Yongzhen Peng (Science of The Total Environment, 2023)

Lithium-induced alterations in soybean nodulation and nitrogen fixation through multifunctional mechanisms - Noman Shakoor; Muzammil Hussain; Muhammad Adeel; Imran Azeem; Muhammad Arslan Ahmad; Muhammad Zain; Peng Zhang; Yuanbo Li; Wang Quanlong; Robert Horton; Yukui Rui (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Neuroprotective α-pyrones from Nigrospora oryzae, an endophytic fungus residing in Taxus chinensis var. mairei - Zi Yun Fan; Jing Peng; Jun Qiao Lou; Yong Chen; Xue Ming Wu; Rui Tan; Ren Xiang Tan (Phytochemistry, 2023)

Evaluation of GPM IMERG and error sources for tropical cyclone precipitation over eastern China - Fengjiao Chen; Rui Wang; Peng Liu; Lu Yu; Yan Feng; Xiaoyi Zheng; Jinlan Gao (Journal of Hydrology, 2023)

Direct regeneration of spent LiFePO4 materials via a green and economical one-step hydrothermal process - Jinyi Yang; Kai Zhou; Rui Gong; Qi Meng; Yingjie Zhang; Peng Dong (Journal of Environmental Management, 2023)

Fabrication of N, O dual-doped ultra-microporous carbon from microalgae for efficient CO2 capture via deep eutectic solvent-assisted hydrothermal carbonization - Rui Huang; Anding Zhong; Kexia Huang; Yujie Yu; Yumu Tang; Peng Xia (Journal of Environmental Chemical Engineering, 2023)

Efficient wastewater disinfection through FeOOH-mediated photo-Fenton reaction: A review - Chen Wang; Peng Shi; Zhaobo Wang; Rui Guo; Junhua You; Hangzhou Zhang (Journal of Environmental Chemical Engineering, 2023)

The protective effect of small black soybean (Vigna Mungo L.) polysaccharide on acetic acid-induced gastric ulcer in SD rats and its impact on gut microbiota and metabolites - Zuanyuan Huang; Mengwei Hu; Xiuyi Peng; Rui Wang; Xiaoxiao Song; Junyi Yin (Food Bioscience, 2023)

Physicochemical stability of lichenan (Usnea longissima) decorated-selenium nanoparticles for cancer chemoprevention - Ziying Yang; Yajie Hu; Panpan Yue; Rui Tian; Huiling Li; Baozhong Lü; Gegu Chen; Feng Peng (Food Bioscience, 2023)

Modeling land use change prediction using multi-model fusion techniques: A case study in the Pearl River Delta, China - Youcheng Song; Haijun Wang; Xiaotao Peng; Duan Sun; Rui Chen (Ecological Modelling, 2023)

Successful start-up of a novel integrated denitrifying phosphorus removal and partial denitrification coupled with anammox process for simultaneous nitrogen and phosphorus removal with fully ordinary suspended sludge - Yunlong Su; Rui Du; Jiao Wang; Junfei Qiao; Xiyao Li; Xiaofei Xue; Zhiqi Cao; Yongzhen Peng (Chemical Engineering Journal, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Chemical constituents from Vitex negundo var. cannabifolia (Sieb. et Zucc.) Hand.-Mazz. (Lamiaceae) and their chemotaxonomic significance - Muhammad Aurang Zeb; Peng-Yun Yang; De-Wen Bi; Wen-Chao Tu; Xiao-Li Li; Rui-Han Zhang; Xing-Jie Zhang; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2023)

Volatile organic compounds during routine production and planned shutdown of a petrochemical refinery: Emission characteristics, source and risk assessment - Yunxia Feng; Guolong Wang; Rui Dong; Bo Li; Dewu Ding; Jinchan Peng; Anshan Xiao (Atmospheric Pollution Research, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Hmox1 is Identified as a Ferroptosis Hub Gene and Associated with the M1 Type Microglia/Macrophage Polarization in Spinal Cord Injury: Bioinformatics and Experimental Validation - Yong Xuan; Kai Peng; Rui Zhu; Yu Kang; Zongsheng Yin (Molecular Neurobiology, 2023)

Changes in Nitrogen-Related Performance Attributes of Winter Wheat Varieties Released Between 1950 and 2020 in Dryland Region of China - Ma Lijuan; Muhammad Fraz Ali; Huang Xiaohu; Peng Zili; Usman Zulfiqar; Wang Rui (Journal of Soil Science and Plant Nutrition, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Dietary supplementation of pyridoxine can enhance the growth performance and improve the protein, lipid utilization efficiency of mandarin fish (Siniperca chuatsi) - Rui-Peng Xie; Xu-Fang Liang; Di Peng; Qi-Wei Zhang; Dong-Liang Wu; Jun-Liang Chen; Ming Zeng (Fish Physiology and Biochemistry, 2023)

Nano-composite system of traditional Chinese medicine for ocular applications: molecular docking and three-dimensional modeling insight for intelligent drug evaluation - Xinyi Jiao; Xingru Peng; Xin Jin; Ning Liu; Yang Yu; Rui Liu; Zheng Li (Drug Delivery and Translational Research, 2023)

Rapid LC-MS/MS detection of 25-hydroxyvitamin D in dried blood spots - Hai-Bo Wang; Xuan Xiao; Wen Dai; Rui Peng; Juan Le; Yu-Qi Feng; Shao-Ting Wang (Analytica Chimica Acta, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

Three Types of Enteromorpha prolifera Bio-Products Based on Different Processing Procedures as Feed Additives in the Diets of Pacific White Shrimp (Litopenaeus vannamei) - Zhibin Zhou; Lubo Wang; Mingqin Dai; Qingyan Gao; Peng Wang; Lili Zhao; Yanlu Li; Rui Xi; Mingchao Pan; Qiang Ma; Houguo Xu; Mengqing Liang; et al. (Fishes, 2023)
A feeding trial was conducted to evaluate the biological activities of Enteromorpha prolifera bio-products in the diets of Pacific white shrimp (Litopenaeus vannamei). Bio-products of E. prolifera included E. prolifera meal, E. prolifera hydrolysate and E. prolifera polysaccharide, which was supplied using different processing procedures. The control diet was supplemented without any E. prolifera bio-products or dietary attractants. Experimental diets were formulated to contain 0.2% and 0.4% of E. prolifera hydrolysate (EPH0.2% and EPH0.4%), 0.03% of E. prolifera polysaccharide (EPP0.03%), 3% of E. prolifera meal (EPM3%), 0.1% of dimethyl-β-propiothetn (DMPT0.1%) and 1% of squid paste (SP1%). Shrimp (~8 g) were randomly distributed in 21 tanks and fed for 44 days. Feed intake showed that 3% of E. prolifera meal and 0.4% of E. prolifera hydrolysate in diets exhibited similar attractant effects as 0.1% of DMPT. Gross qualitative observation showed that the abundance of lipid droplets decreased in hepatopancreas of the EPH0.4% and EPM3% groups, which were supported by hepatopancreas triacylglycerol (TG), where significantly lower concentrations were observed in the EPH0.4% and EPM3% groups compared with the control group. Similarly, TG and low-density lipoprotein cholesterol in serum significantly decreased in the EPH0.4%, EPP0.03% and EPM3% groups compared to the control group. Supplemental E. prolifera bio-products resulted in significantly higher serum glutathione level of EPP0.03% or superoxide dismutase activities of EPH0.4% and EPM3%, but significantly lower serum malondialdehyde level of EPM3%. In addition, tnf-α expression in hepatopancreas was significantly down-regulated in shrimp fed the EPH0.2%, EPH0.4% and EPM3% diets. Based on survival analysis, E. prolifera bio-products improved the resistance of shrimp to hypoxic stresses. Thus, this study confirmed that bio-products of E. prolifera supplied using different processing procedures could be used to reduce the amount of E. prolifera in feed of shrimp without compromising their biological functions.

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

A novel method of desynchronized operation of sails for ship wind-assisted propulsion system - Rui Zhang; Lianzhong Huang; Guisheng Peng; Ranqi Ma; Kai Wang; Feng Tian; Qiushi Song (Ocean Engineering, 2023)

A tholeiitic damp parental magma for the Miyi mafic intrusion: Implications for water heterogeneity in the Emeishan large igneous province - Ying Xia; Yue Chen; An-Qing Chen; Hui-Juan Peng; Rui-Qiang Wang; Dong-Xing Han (Lithos, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Insights into brain perceptions of the different taste qualities and hedonic valence of food via scalp electroencephalogram - Tianyi Yang; Peng Zhang; Lidong Xing; Jin Hu; Rui Feng; Junjie Zhong; Weitao Li; Yizhi Zhang; Qiaoqiao Zhu; Yamin Yang; Fan Gao; Zhiyu Qian (Food Research International, 2023)

Quantitative proteomics analysis on the meat quality of processed pale, soft, and exudative (PSE)-like broiler pectoralis major by different heating methods - Tianyi Yang; Yamin Yang; Peng Zhang; Weitao Li; Qingfeng Ge; Hai Yu; Mangang Wu; Lidong Xing; Zhiyu Qian; Fan Gao; Rui Liu (Food Chemistry, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Pilot-scale demonstration of self-enrichment of anammox bacteria in a two-stage nitrification-denitrification suspended sludge system treating municipal wastewater under extremely low nitrogen loading rate - Yunlong Su; Rui Du; Jiao Wang; Xiyao Li; Qiong Zhang; Xiaofei Xue; Yongzhen Peng (Bioresource Technology, 2023)

Role of sonic hedgehog signaling pathway in the regulation of ion channels: focus on its association with cardio-cerebrovascular diseases - Ming-Rui Li; Xiu-Ju Luo; Jun Peng (Journal of Physiology and Biochemistry, 2023)

Molecular dynamics simulation on the dissolution and diffusion characteristics of FeCrAl alloy in liquid LBE - Lu Xie; Guang Da Wu; Qing Peng; Wen Rui Wang (Annals of Nuclear Energy, 2023)

High-performance Cu/Mn modified ceramsite as a persulfate activator to degrade oxytetracycline in batch Erlenmeyer flask and continuous-flow fixed-bed column systems: An exploration of its practicability and non-radical mechanisms - Huang-gen Yang; Mang Lu; Xue-jiao Wu; Rui-ting Dong; Tao-peng Luo; Hui-hua Zhong (Chemosphere, 2023)

Nonthermal plasma coupled with liquid-phase UV/Fe–C for chlorobenzene removal - Caihong Qin; Chaochao Jiang; Rongrong Liu; Jiayu Huang; Rui Yu; Peng Zhang (Chemosphere, 2023)

A petal–cylindrical seismic metamaterial occupying low-frequency wide bandgaps in horizontally stratified soils - Muhammad Muzamil; Hongwu Yang; Rui Xu; Yi Zeng; Pai Peng; Qiujiao Du (Wave Motion, 2023)

Recent innovations in microplastics and nanoplastics removal by coagulation technique: Implementations, knowledge gaps and prospects - Imran Ali; Xiao Tan; Yue Xie; Changsheng Peng; Juying Li; Iffat Naz; Zhipeng Duan; Peng Wan; Jiang Huang; Jia Liang; Zhu Rui; Yinlan Ruan (Water Research, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Elastic properties of amphibole at high pressure: A new explanation of the low velocities anomaly in the mantle wedges - Jikai Zhang; Duojun Wang; Nao Cai; Rui Zhang; Peng Chen (Tectonophysics, 2023)

The sound velocity of garnet at high pressure: Implications for high velocity anomalies in cold subducting slabs - Peng Chen; Duojun Wang; Nao Cai; Jikai Zhang; Rui Zhang; Ruixin Zhang; Kenan Han; Yang Cao (Tectonophysics, 2023)

Effect of Triton X-100 on Shiraia laccase production and its application in triclosan biodegradation - Rui Peng Cong; Yan Hua Guo; Jian Qin Zhou; Jian Wen Wang (Sustainable Chemistry and Pharmacy, 2023)

Source identification and migration fate of metal(loid)s in soil and groundwater from an abandoned Pb/Zn mine - Chiyue Huang; Zhaohui Guo; Tianshuang Li; Rui Xu; Chi Peng; Zilun Gao; Linjian Zhong (Science of The Total Environment, 2023)

Modifying engineered nanomaterials to produce next generation agents for environmental remediation - Muhammad Arslan Ahmad; Muhammad Adeel; Noman Shakoor; Rabia Javed; Muhammad Ishfaq; Yutao Peng; Muhammad Zain; Imran Azeem; Ilyas Ali; Muhammad Usman; Zihao Wu; Gholamreza Gohari; et al. (Science of The Total Environment, 2023)

Distribution, source identification, and health risk of emerging organic contaminants in groundwater of Xiong'an New Area, Northern China - Rui An; Bin Li; Sining Zhong; Guyu Peng; Jie Li; Ruoqi Ma; Qian Chen; Jinren Ni (Science of The Total Environment, 2023)

Assessing carbon cap-and-trade policies on hybrid renewable energy investments: Implications for pricing and capacity decisions - Zhaobiao Rui; Weicai Peng; Ximei Qin; Jun Wang (Resources Policy, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Nano-agriculture and nitrogen cycling: Opportunities and challenges for sustainable farming - Quanlong Wang; Li Gao; Yuanbo Li; Noman Shakoor; Yi Sun; Yaqi Jiang; Guikai Zhu; Fayuan Wang; Yunze Shen; Yukui Rui; Peng Zhang (Journal of Cleaner Production, 2023)

Metagenomic analysis reveals microbial metabolic potentials alterations under antibiotic stress during sludge anaerobic digestion - Yinping Xiang; Weiping Xiong; Rui Xu; Zhaohui Yang; Yanru Zhang; Meiying Jia; Haihao Peng (Journal of Environmental Chemical Engineering, 2023)

A novel calcium peroxide/attapulgite-Fe(II) process for high concentration phosphate removal and recovery: Efficiency and mechanism - Jun Luo; Jia Peng; Zhenxing Zhong; Xuejun Long; Jiazhi Yang; Rui Li; Jun Wan (Journal of Environmental Management, 2023)

Characterization of different grades of Jiuqu hongmei tea based on flavor profiles using HS-SPME-GC-MS combined with E-nose and E-tongue - Qi Peng; Shanshan Li; Huajun Zheng; Kai Meng; Xi Jiang; Rui Shen; Jingrun Xue; Guangfa Xie (Food Research International, 2023)

Oat bran prevents high-fat-diet induced muscular dysfunction, systemic inflammation and oxidative stress through reconstructing gut microbiome and circulating metabolome - Rui Dong; Kejie Peng; Lin Shi; Qianwen Niu; Hamad Rafique; Yuan Liu; Li Yuan; Liang Zou; Lu Li; Maria Cristina Messia; Xinzhong Hu (Food Research International, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Dual network hydrogel coatings based on recombinant mussel protein with enhanced antibacterial and super-lubrication properties for urinary catheter applications - Yubo Hu; Youzhi Qiao; Peng Lei; Yian Gu; Liang Sun; Yibin Qiu; Sha Li; Hong Xu; Rui Wang (Chemical Engineering Journal, 2023)

Simultaneous nitrite production and phosphorus removal by partial denitrification-hydroxyapatite (PD-HAP) coupled process from high-nitrate wastewater - Yu Lan; Rui Du; Xiaoyan Fan; Shenbin Cao; Yongzhen Peng (Chemical Engineering Journal, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Development of a novel fluorescent aptasensor based on the interaction between hexagonal β-Co(OH)2 nanoplates and nitrogen-doped carbon dots for ultrasensitive detection of patulin - Qi Sun; Zhijuan Li; Ningxin Liu; Yuting Zhou; Fuyan Zhang; Shuang Li; Peng Jin; Rui Xiang; Tao Le (Analytica Chimica Acta, 2023)

Ultra-sensitive photoelectrochemical biosensor for determination of African swine fever virus based on surface plasmon resonance - Ruishuang Yuan; Jie Wei; Rui Geng; Bin Li; Wei Xiong; Xueen Fang; Peng Lü; Kun Wang (Analytica Chimica Acta, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Epidemiology, genetic diversity, and evolutionary dynamics of Tembusu virus - Peng Zhou; Bin Ma; Yuan Gao; Yumin Xu; Zhuofei Li; Hui Jin; Rui Luo (Archives of Virology, 2023)

Phylogenetic distance–decay patterns are not explained by local community assembly processes in freshwater lake microbial communities - Yian Gu; Zhidan Li; Peng Lei; Rui Wang; Hong Xu; Ville‐Petri Friman (Environmental Microbiology, 2023)
While water and sediment microbial communities exhibit pronounced spatio‐temporal patterns in freshwater lakes, the underlying drivers are yet poorly understood. Here, we evaluated the importance of spatial and temporal variation in abiotic environmental factors for bacterial and microeukaryotic community assembly and distance–decay relationships in water and sediment niches in Hongze Lake. By sampling across the whole lake during both Autumn and Spring sampling time points, we show that only bacterial sediment communities were governed by deterministic community assembly processes due to abiotic environmental drivers. Nevertheless, consistent distance–decay relationships were found with both bacterial and microeukaryotic communities, which were relatively stable with both sampling time points. Our results suggest that spatio‐temporal variation in environmental factors was important in explaining mainly bacterial community assembly in the sediment, possibly due lesser disturbance. However, clear distance–decay patterns emerged also when the community assembly was stochastic. Together, these results suggest that abiotic environmental factors do not clearly drive the spatial structuring of lake microbial communities, highlighting the need to understand the role of other potential drivers, such as spatial heterogeneity and biotic species interactions.

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Identification of priority pollutants and key factors affecting environmental risks of lead‑zinc mine tailing sites - Jing-yu Peng; Shuai Zhang; Yu-jing Wang; Rui-feng Zhao; Yi-ling Zhou; Jian-wei Zhou (Science of The Total Environment, 2023)

Rare loss-of-function variants reveal threshold and multifactorial inheritance of dextrocardia - Zhongzhong Chen; Yunqian Gao; Lei Lu; Nan Li; Pei Liu; Rui Peng; Lingling Liu; Hefeng Huang; Qihua Fu; Haifa Hong; Jianguo Zhang; Hongyan Wang (Science Bulletin, 2023)

Preparation of magnesium potassium phosphate cement from municipal solid waste incineration fly ash and lead slag co-blended: Ca-induced crystal reconstruction process and Pb-Cl synergistic solidification mechanism - Shiwei Liu; Xing Cao; Weichen Yang; Runjie Liu; Lin Fang; Rui Ma; Juan Peng; Shuaifei Zheng; Fei Ji (Journal of Hazardous Materials, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Structure, rheology, and antifreeze property of the exopolysaccharide from Naematelia aurantialba through basidiospore fermentation - Tao Sun; Xiaoyi Xu; Yuhang Ma; Hao jiang; Kai Yang; Rui Wang; Yian Gu; Sha Li; Yibin Qiu; Dafeng Sun; Hong Xu; Peng Lei (Food Hydrocolloids, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Remarkable bioactivity, bio-tribological, antibacterial, and anti-corrosion properties in a Ti-6Al-4V-xCu alloy by laser powder bed fusion for superior biomedical implant applications - Jiang Ju; Rui Zan; Zhao Shen; Chenchen Wang; Peng Peng; Jun Wang; Baode Sun; Bo Xiao; Qian Li; Shaofei Liu; Tao Yang (Chemical Engineering Journal, 2023)

The biocontrol agent Bacillus velezensis T-5 changes the soil bacterial community composition by affecting the tomato root exudate profile - Yian Gu; Weina Liang; Zhidan Li; Sijie Liu; Sun Liang; Peng Lei; Rui Wang; Nan Gao; Sha Li; Zongqi Xu; Hong Xu (Plant and Soil, 2023)

Estimation of in-season nitrogen requirement for drip-irrigated spring maize without or with straw incorporation using critical nitrogen dilution curve - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Plant and Soil, 2023)

Effects of EDTA and Organic Acids on Physiological Processes, Gene Expression Levels, and Cadmium Accumulation in Solanum nigrum Under Cadmium Stress - Wanhong Liu; Ting Yu; Hanping Cao; Xiang Peng; Ya Yang; Rui Li (Journal of Soil Science and Plant Nutrition, 2023)

Nafamostat mesilate prevented caerulein-induced pancreatic injury by targeting HDAC6-mediated NLRP3 inflammasome activation - Peng Chen; Li-Jun Zhao; Ling Huang; Wen-Qi He; Ying-Rui Tang; Yi Liu; Jian-Dong Ren (Inflammation Research, 2023)

Silicified Microorganisms and Microorganism-Like Particles in the Groundwater of an Abandoned Coal Mine - Guangyu Shao; Changsuo Li; Rui Liu; Peng Zhang; Lei Zuo; Yaqin Wang (Mine Water and the Environment, 2023)

Purification of conchocelis of Neoporphyra haitanensis by the method of dominant Bacteria enrichment comprehensive treatment - Mingjie Ma; Qiqin Liu; Lin Huang; Peng Zhang; Haimin Chen; Juanjuan Chen; Qijun Luo; Tiegan Wang; Rui Yang (Aquaculture, 2023)

Can China achieve its 2030 and 2060 CO2 commitments? Scenario analysis based on the integration of LEAP model with LMDI decomposition - Yimin Huang; Yuan Wang; Jiaoting Peng; Fan Li; Lin Zhu; Huihui Zhao; Rui Shi (Science of The Total Environment, 2023)

Evaluation of sludge anaerobic fermentation driving partial denitrification capability: In view of kinetics and metagenomic mechanisms - Qingtao Liu; Cong Li; Jiarui Fan; Yongzhen Peng; Rui Du (Science of The Total Environment, 2023)

Dynamic probabilistic risk assessment of emergency response for intelligent coal mining face system, case study: Gas overrun scenario - Yan Zhang; Yu-Hao Wang; Xu Zhao; Rui-Peng Tong (Resources Policy, 2023)

Antibacterial, antiviral, and biodegradable collagen network mask for effective particulate removal and wireless breath monitoring - Peng Zhao; Rui Wang; Jun Xiang; Jinwei Zhang; Xiaodong Wu; Chaojian Chen; Gongyan Liu (Journal of Hazardous Materials, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

A “smart-sensing” bactericidal protein-based Pickering emulsion - Lishan Yao; Rui Wang; Shurui Peng; Zhenbin Liu; Hongbo Li; Dan Xu; Liangbin Hu; Haizhen Mo (Journal of Food Engineering, 2023)

Construction of S-scheme Zn0.2Cd0.8S/biochar aerogel architectures for boosting photocatalytic hydrogen production under sunlight irradiation - Chonghai Deng; Lulu Peng; Xiaohui Ling; Tao Wang; Rui Xu; Yibin Zhu; Chenchen Wang; Xuehui Qian; Lili Wang; Yiping Wu; Hanmei Hu; Yongsheng Han (Journal of Cleaner Production, 2023)

Spatiotemporal clustering analysis of shared electric vehicles based on trajectory data for sustainable urban governance - Lewen Bao; Zonglin Liu; Rui Miao; Zhihua Chen; Bo Zhang; Peng Guo; Yuze Ma (Journal of Cleaner Production, 2023)

Enhanced recovery of germanium(IV) from zinc residue leachate by tartaric acid functionalized chitosan: Experiments and DFT calculation - Hongrui Xiang; Zhihui Yang; Xiaobo Min; Yanjie Liang; Cong Peng; Xiaoyun Liu; Rui Yuan; Qingwei Wang; Feiping Zhao (Hydrometallurgy, 2023)

Analytical study on heavy metal output fluxes and source apportionment of a non-ferrous smelter in southwest China - Chenchen Li; Peng Dong; Jin Yan; Rui Gong; Qi Meng; Jun Yao; Hanjing Yu; Yaoqiang Ma; Bang Liu; Ruosong Xie (Environmental Pollution, 2023)

Highly stretchable phase change composites for simultaneous health monitoring and thermotherapy - Yi-Cun Zhou; Jie Yang; Wu-Di Li; Peng Yu; Zheng-Min Zhang; Lu Bai; Rui-Ying Bao; Wei Yang (Chemical Engineering Journal, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Seasonal associations between air pollutants and influenza in 10 cities of southern China - Rui Zhang; Yonghong Li; Peng Bi; Siyuan Wu; Zhibin Peng; Yujie Meng; Yu Wang; Songwang Wang; Yushu Huang; Juan Liang; Jing Wu (International Journal of Hygiene and Environmental Health, 2023)

Experimental and numerical study on the ignition delay times of methane/propane mixtures diluted in carbon dioxide - Wenxiang Xia; Chun Zou; Yi Yuan; Rui Fu; Jiacheng Liu; Chao Peng (Fuel, 2023)

Soil variables and reflected light revealed the plasticity of grape and wine composition: Regulation of the flavoromics under inner row gravel covering - Meng-Bo Tian; Wan-Hui Ma; Nong-Yu Xia; Jing Peng; Rui-Qi Hu; Chang-Qing Duan; Fei He (Food Chemistry, 2023)

Duox mediated ROS production inhibited WSSV replication in Eriocheir sinensis under short-term nitrite stress - Rui Jia; Xiaoling Dai; Yanfang Li; Xintong Yang; Xiuwen Min; Derun Quan; Peng Liu; Xin Huang; Jiachun Ge; Qian Ren (Aquatic Toxicology, 2023)

The increasing risk of future simultaneous droughts over the Yangtze River basin based on CMIP6 models - Ying Zhang; Xin Hu; Zengxin Zhang; Rui Kong; Zhenhua Peng; Qi Zhang; Xi Chen (Stochastic Environmental Research and Risk Assessment, 2023)

Selenium toxicity and bioaccumulation in selenium-enriched fly (Chrysomya megacephala) maggots - Rui Jie Peng; Chao Zheng; Zhan Biao Yang; Xiao Xun Xu; Ming Hung Wong; Yu Bon Man; Zhang Cheng (Environmental Geochemistry and Health, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

Compound and successive events of extreme precipitation and extreme runoff under heatwaves based on CMIP6 models - Peng Sun; Yifan Zou; Rui Yao; Zice Ma; Yaojin Bian; Chenhao Ge; Yinfeng Lv (Science of The Total Environment, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

China's optimal development pathway of intermittent renewable power towards carbon neutrality - Bai-Chen Xie; Rui-Yu Zhang; Xian-Peng Chen (Journal of Cleaner Production, 2023)

Sensing property of Pt-doped Janus SnSSe monolayer upon thermal runaway gases in the lithium-ion battery with effects of biaxial strains and electric fields - Di Zheng; Wenjing Peng; Rui Wu; Shunan Quan; Lijuan Qian; Hao Cui (Journal of Environmental Chemical Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

Rapid identification of high and low cadmium (Cd) accumulating rice cultivars using machine learning models with molecular markers and soil Cd levels as input data - Zhong Tang; Ting-Ting You; Ya-Fang Li; Zhi-Xian Tang; Miao-Qing Bao; Ge Dong; Zhong-Rui Xu; Peng Wang; Fang-Jie Zhao (Environmental Pollution, 2023)

Paleoproterozoic accretion and assembly of the Western Block of North China: A new model - Changqing Yin; Guochun Zhao; Wenjiao Xiao; Shoufa Lin; Rui Gao; Jian Zhang; Jiahui Qian; Peng Gao; Hengzhong Qiao; Wenxuan Li (Earth-Science Reviews, 2023)

Verifying the applicability of PD/A unit for ultimate sidestream and mainstream polishing: Operating performance, granular characteristics and active microbes - Xiangchen Li; Rui Du; Jingwen Zhang; Chan Chai; Xiyao Li; Qiong Zhang; Shuying Wang; Junfei Qiao; Yongzhen Peng (Chemical Engineering Journal, 2023)

Complete nitrogen removal from low-strength wastewater via double nitrite shunt coupling anammox and endogenous nitrate respiration: Functional metabolism and electron transport - Qiongpeng Dan; Rui Du; Tong Wang; Tiantian Sun; Honggui Han; Xiaorong Zhu; Xiyao Li; Qiong Zhang; Yongzhen Peng (Chemical Engineering Journal, 2023)

One-step synthesis of efficient manganese-based oxide catalyst for ultra-rapid CO2 absorption in MDEA solutions - Xiaowen Zhang; Shangshang Zhang; Zhan Tan; Sisi Zhao; Yi Peng; Cong Xiang; Wenbo Zhao; Rui Zhang (Chemical Engineering Journal, 2023)

Angiotensin Type 2 Receptor Pharmacological Agonist Relieves Neurocognitive Deficits via Reducing Neuroinflammation and Microglial Engulfment of Dendritic Spines - Liang Shen; Dan-yang Chen; Qian-qian Lou; Peng Cao; Rui Hu; Yan Jin; Di Wang; Shan-shan Hu (Journal of Neuroimmune Pharmacology, 2023)

Causal associations of circulating Helicobacter pylori antibodies with stroke and the mediating role of inflammation - Xingzhi Guo; Peng Tang; Xin Zhang; Rui Li (Inflammation Research, 2023)

Large-scale characteristics of thermokarst lakes across the source area of the Yellow River on the Qinghai-Tibetan Plateau - Wen-hui Liu; Guang-hao Zhou; Hai-rui Liu; Qing-peng Li; Chang-wei Xie; Qing Li; Jian-yun Zhao; Qi Zhang (Journal of Mountain Science, 2023)

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

Robustness and stability of acetate-driven partial denitrification (PD) in response to high COD/NO3−-N - Shenbin Cao; Yu Lan; Rui Du; Yongzhen Peng (Chemosphere, 2023)

CuFe2O4/diatomite actuates peroxymonosulfate activation process: Mechanism for active species transformation and pesticide degradation - Peng Xu; Rui Wei; Peng Wang; Xiang Li; Chunyan Yang; Tianyao Shen; Tong Zheng; Guangshan Zhang (Water Research, 2023)

Plant litter strengthens positive biodiversity–ecosystem functioning relationships over time - Wei-Ping Zhang; Dario Fornara; Hao Yang; Rui-Peng Yu; Ragan M. Callaway; Long Li (Trends in Ecology & Evolution, 2023)

The impact of behavior safety management system on coal mine work safety: A system dynamics model of quadripartite evolutionary game - Yan Zhang; Si-Xia Wang; Jian-Ting Yao; Rui-Peng Tong (Resources Policy, 2023)

Environmental and economic impacts of drone-assisted truck delivery under the carbon market price - Zhiyi Meng; Yuting Zhou; Eldon Y. Li; Xinying Peng; Rui Qiu (Journal of Cleaner Production, 2023)

Long-term straw incorporation regulates greenhouse gas emissions from biodegradable film farmland, improves ecosystem carbon budget and sustainable maize productivity - Rui Qian; Ru Guo; Muhammad Asad Naseer; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Impact of clayey sediment compaction on pore water evolution and the release of iron - Yanjun Liu; Teng Ma; Juan Chen; Ziqi Peng; Cong Xiao; Wenkai Qiu; Rui Liu; Yao Du (Applied Geochemistry, 2023)

Green finance network evolution and prediction: fresh evidence from China - Rui Ding; Yiming Du; Linyu Du; Jun Fu; Shihui Chen; Kexin Wang; Wenqian Xiao; Lina Peng; Juan Liang (Environmental Science and Pollution Research, 2023)

Examination of the transmission mechanism of energy prices influencing carbon prices: an analysis of mediating effects based on demand heterogeneity - Rui Wang; Xinglin Zhao; Kerong Wu; Sha Peng; Si Cheng (Environmental Science and Pollution Research, 2023)

Aggregation and construction mechanisms of microbial extracellular polymeric substances with the presence of different multivalent cations: Molecular dynamic simulation and experimental verification - Sainan Peng; Zhiyue Wang; Pingfeng Yu; Guiying Liao; Rui Liu; Dongsheng Wang; Weijun Zhang (Water Research, 2023)

Assessing the effects of short-term traffic restriction policies on traffic-related air pollutants - Xiao-Rui Fang; Xing-Hang Zhu; Xing-Zhou Li; Zhong-Ren Peng; Hu Qingyao; Hong-Di He; AJ Yuan Chen; Huang Cheng (Science of The Total Environment, 2023)

Responses of agricultural drought to meteorological drought under different climatic zones and vegetation types - Peng Sun; Ruilin Liu; Rui Yao; Hao Shen; Yaojin Bian (Journal of Hydrology, 2023)

Thickness-dependent release of microplastics and phthalic acid esters from polythene and biodegradable residual films in agricultural soils and its related productivity effects - Aimee Grace Uzamurera; Peng-Yang Wang; Ze-Ying Zhao; Xiu-Ping Tao; Rui Zhou; Wen-Ying Wang; Xiao-Bin Xiong; Song Wang; Kiprotich Wesly; Hong-Yan Tao; You-Cai Xiong (Journal of Hazardous Materials, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Role of moveable guide vane with various configurations in controlling the vortex-induced vibration of twin-box girder suspension bridges: An experimental investigation - Rui Zhou; Peng Lu; Xiaodong Gao; Yaojun Ge; Yongxin Yang; Lihai Zhang (Engineering Structures, 2023)

High adaptability and stability FeCo2O4/diatomite composite for efficient peroxymonosulfate activation: Performance, water matrix impact, and mechanism - Peng Xu; Xiang Li; Rui Wei; Chunyan Yang; Tianyao Shen; Peng Wang; Guangshan Zhang (Chemical Engineering Journal, 2023)

Fluid evolution and ore genesis of the Tiantangshan granite-related vein-type Rb-Sn-W deposit, south China: constraints from LA-ICP-MS analyses of fluid inclusions - Hong-Wei Peng; Hong-Rui Fan; Pilar Lecumberri-Sanchez; Jian-Qing Lai; Huan-Long Hu; Ting-Guang Lan; Xing-Hui Li (Mineralium Deposita, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

Sandstorms damage the photosynthetic activities of Haloxylon ammodendron seedlings - Shengbo Shi; Dangwei Zhou; Rui Shi; Tao Sun; Fanglin Wang; Xiuzhen Gao; Yunian Zhang; Peng Zhao; Gaoxing Xu; Jinnian Tang (Acta Physiologiae Plantarum, 2023)
Haloxylon ammodendron is a preferred shrub species for buffering against wind and fixing sand in arid sandy areas of northwest China. To determine whether sandstorms cause damage to H. ammodendron seedlings, we investigated the effects of wind-blown sands on the photosynthetic function of H. ammodendron by simulating sand-carrying wind in the wind tunnel. The results showed that photosystem II (PSII) non-photochemical quenching ( NPQ ) was sensitive to wind erosion, and sustained blowing of sand-carrying winds enhanced NPQ reduction. The rapidly relaxing quenching NPQ f made up the majority component of NPQ ; the NPQ f / NPQ ratio was approximately 64.4% in the sand-free wind group and nearly 56.2% in the sand-carrying wind group. The distribution of the quantum efficiency of the excitation energy indicated that the relative proportions of the quantum yield of PSII photochemistry Φ PSII , the quantum yield of quenching due to light-induced Φ NPQ , and non-light-induced Φ NO were influenced by both wind erosion and light intensity; the sand-carrying wind resulted in a relative decrease in Φ NPQ and a corresponding increase in Φ NO . The maximum quantum efficiency of PSII photochemistry F v / F m was relatively stable in the sand-free wind group, with an average value of approximately 0.81. Compared to sand-free wind, sand-carrying winds caused remarkable decreases in F v / F m . Light intensity was the main factor affecting Φ PSII , Φ NPQ , and relative electron transport rate ( rETR ); there was no interaction effect between the duration of sand-carrying wind and light intensity. Taken together, wind-blown sands cause irreversible damage to the photosynthesis of H. ammodendron seedlings, which is the main factor restricting population regeneration in shelterbelts.

Potential causes of partial-denitrification (PD) granular sludge breakdown under high nitrate loading rates - Rui Du; Qingtao Liu; Yongzhen Peng; Shenbin Cao (Science of The Total Environment, 2023)

Managing straw and nitrogen fertilizer based on nitrate threshold for balancing nitrogen requirement of maize and nitrate residue - Ru Guo; Rui Qian; Fei Han; Abdul Khaliq; Sadam Hussain; Ling Yang; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Journal of Environmental Management, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Iron-based nanomaterials reduce cadmium toxicity in rice (Oryza sativa L.) by modulating phytohormones, phytochelatin, cadmium transport genes and iron plaque formation - Pingfan Zhou; Peng Zhang; Mengke He; Yu Cao; Muhammad Adeel; Noman Shakoor; Yaqi Jiang; Weichen Zhao; Yuanbo Li; Mingshu Li; Imran Azeem; Like Jia; et al. (Environmental Pollution, 2023)

Slab dehydration and magmatism in the Kurile arc as a function of depth: An investigation based on B-Sr-Nd-Hf isotopes - Hong-Yan Li; Chao Xie; Jeffrey G. Ryan; Chuan-Mao Yang; Rui-Peng Zhao; Chao Zhang; Yi-Gang Xu (Chemical Geology, 2023)

Differences in the patterns and mechanisms of leaf and ecosystem-scale water use efficiencies on the Qinghai-Tibet Plateau - Xiang Wang; Guo Chen; Mingquan Wu; Xiaozhen Li; Qi Wu; Peng Wang; Hui Zeng; Rui Yang; Xiaolu Tang (CATENA, 2023)

Superior nitrogen removal and efficient sludge reduction via partial nitrification-anammox driven by addition of sludge fermentation products for real sewage treatment - Jinjin Liu; Qiong Zhang; Shuying Wang; Xiyao Li; Rui Wang; Yongzhen Peng (Bioresource Technology, 2023)

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

Identification of HQT gene family and their potential function in CGA synthesis and abiotic stresses tolerance in vegetable sweet potato - Milca Banda Medison; Rui Pan; Ying Peng; Rudoviko Galileya Medison; Abdullah Shalmani; XinSun Yang; Wenying Zhang (Physiology and Molecular Biology of Plants, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Caffeoyl esters from Aruncus sylvester and their improvement in movement disorder of MPTP-induced zebrafish embryos - Jiaoyang Li; Rui Peng; Yi Zhu; Meijun Pang; Yanfang Su (Phytochemistry Letters, 2023)

Dynamic stiffness formulation for free vibration analysis of rotating cross-ply laminated combined elliptical-cylindrical-conical shell - Qing Peng; Qingshan Wang; Zhengxiong Chen; Rui Zhong; Tao Liu; Bin Qin (Ocean Engineering, 2023)

Projecting multi-attribute flood regime changes for the Yangtze River basin - Chen Zhang; Fengyun Sun; Sanjib Sharma; Peng Zeng; Alfonso Mejia; Yongpeng Lyu; Jun Gao; Rui Zhou; Yue Che (Journal of Hydrology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Predicting future coastal land use/cover change and associated sea-level impact on habitat quality in the Northwestern Coastline of Guinea-Bissau - Namir Domingos Raimundo Lopes; Tianxin Li; Peng Zhang; Nametso Matomela; Harrison Odion Ikhumhen; Rui M. Sá (Journal of Environmental Management, 2023)

Quantitative determination of d-psicose based on flexible copper film materials and electrochemical scanning methods - Jingyu Zhang; Chengxiang Yong; Xiangchen Li; Runhao Zhu; Yongzhi Lai; Rui Peng; Ruizhi Zhao; Tianxi Yu; Jingyuan Ning; Siyi Xiong; Guohua Hui; Peng Wu (Food Chemistry, 2023)

A highly-sensitive sensor based on carbon nanohorns@reduced graphene oxide coated by gold platinum core–shell nanoparticles for electrochemical detection of carbendazim in fruit and vegetable juice - Wenzhe Li; Peixuan Wang; Beibei Chu; Xingguang Chen; Zhengcong Peng; Jiyang Chu; Rui Lin; Qianhui Gu; Jian Lu; Dianhui Wu (Food Chemistry, 2023)

Endogenous partial denitritation as an efficient remediation to unstable partial nitritation-anammox (PNA) process: Bacteria enrichment and superior robustness - Qiongpeng Dan; Rui Du; Tong Wang; Tiantian Sun; Xiyao Li; Qiong Zhang; Yongzhen Peng (Chemical Engineering Journal, 2023)

Effect of the acid site in the catalytic degradation of volatile organic compounds: A review - Caihong Pang; Rui Han; Yun Su; Yanfei Zheng; Mingke Peng; Qingling Liu (Chemical Engineering Journal, 2023)

Metagenomics-based interpretation of selective bioaugmentation promoting partial-denitrification coupling with anammox process reactivation in suspended sludge system - Cong Li; Qingtao Liu; Jiarui Fan; Yongzhen Peng; Rui Du (Chemical Engineering Journal, 2023)

Rapid and massive fractionation of hemicelluloses for purifying cellulose at room temperature by tetramethylammonium hydroxide - Rui Tian; Bolang Zhu; Qiaoling Liu; Yajie Hu; Ziying Yang; Jun Rao; Yuying Wu; Baozhong Lü; Jing Bian; Feng Peng (Bioresource Technology, 2023)

Extending reaction duration has minor influence on nitrite production in partial-denitrification process - Rui Du; Cong Li; Yongzhen Peng; Shenbin Cao (Bioresource Technology, 2023)

An achieved strategy for magnetic biochar for removal of tetracyclines and fluoroquinolones: Adsorption and mechanism studies - Xianzhao Zhang; Dawei Zhen; Fengmao Liu; Rui Chen; Qingrong Peng; Zongyi Wang (Bioresource Technology, 2023)

Experimental Study of Vibration Reduction Effect of Barrier Holes Under Blasting - Jianbo Zhu; Rui Zhao; Yashi Li; Yankun Ma; Jianxin Wang; Qi Peng; Jun Guo (Rock Mechanics and Rock Engineering, 2023)

Long-term cycles of the Solar System concealed in the Mesozoic sedimentary basin record - Rui Zhang; Zhijun Jin; Michael Gillman; Quanyou Liu; Ren Wei; Peng Li; Zhihui Zhang (Science China Earth Sciences, 2023)

The protective effect of drying on the cryopreservation of Neoporphyra haitanensis - Haike Qian; Qijun Luo; Juanjuan Chen; Rui Yang; Tiegan Wang; Peng Zhang; Haimin Chen (Journal of Applied Phycology, 2023)

Ameliorating C and N balance without loss of productivity by applying mulching measures in rainfed areas - Zihan Liu; Bingfan Wang; Zhaoyang Li; Chenxu Zhao; Rui Qian; Fangyuan Huang; Peng Zhang; Hui Li; ZhiKuan Jia (Agriculture, Ecosystems & Environment, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Calculation method and mechanism of ultimate side resistance of screw pile - Hong-wei Ma; Li Liu; Peng Wang; Song Yuan; Qing-rui He; Xiao-li Yang (Marine Georesources & Geotechnology, 2023)

Wastewater treatment by anodic oxidation in electrochemical advanced oxidation process: Advance in mechanism, direct and indirect oxidation detection methods - Rui Fu; Peng-Shuang Zhang; Yuan-Xing Jiang; Lin Sun; Xu-Hui Sun (Chemosphere, 2023)

Salicylic acid enhances the resistance of Neoporphyra haitanensis to pathogen Vibrio mediterranei 117-T6 - Shanshan Zhu; Zhen Jin; Juanjuan Chen; Rui Yang; Qijun Luo; Tiegan Wang; Peng Zhang; Haimin Chen (Aquaculture, 2023)

Contamination vertical distribution and key factors identification of metal(loid)s in site soil from an abandoned Pb/Zn smelter using machine learning - Zhaohui Guo; Yunxia Zhang; Rui Xu; Huimin Xie; Xiyuan Xiao; Chi Peng (Science of The Total Environment, 2023)

Revealing the driving synergistic degradation mechanism of Rhodococcus sp. B2 on the bioremediation of pretilachlor-contaminated soil - Hongming Liu; Shiyan Liu; Huijun Liu; Mengna Liu; Xiaye Yin; Peng Lu; Qing Hong; Aimin Liu; Rui Wan; Shangping Fang (Science of The Total Environment, 2023)

Rapid enrichment of anammox bacteria and transformation to partial denitrification/anammox with nitrification/denitrification sludge - Yunlong Su; Yongzhen Peng; Jiao Wang; Qiong Zhang; Xiyao Li; Shuying Wang; Xiaofei Xue; Rui Du (Science of The Total Environment, 2023)

Starting up anammox system with high efficiency nitrogen removal at low temperatures: Performance optimization, sludge characterization and microbial community analysis - Liurui Peng; Rui Shi; Youqi Tao; Qian Huang; Maoyuan Yang; Yuecheng He; Wenlai Xu (Journal of Environmental Management, 2023)

Habitat quality dynamics in China's first group of national parks in recent four decades: Evidence from land use and land cover changes - Xin Chen; Le Yu; Yue Cao; Yidi Xu; Zhicong Zhao; Youbo Zhuang; Xuehua Liu; Zhenrong Du; Tao Liu; Bo Yang; Lu He; Hui Wu; et al. (Journal of Environmental Management, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Mobilization of water affecting formation and dissociation of hydrate in clay sediment - Peng Zhang; Xueping Chen; Lianhai Zhang; Shuaijun Li; Wenting Chen; Qingbai Wu; Shuanshi Fan; Rui Bao; Cuicui Mu (Chemical Engineering Journal, 2023)

Fluoroalkane modified cationic polymers for personalized mRNA cancer vaccines - Junyan Li; Yuanyuan Wu; Jian Xiang; Hairong Wang; Qi Zhuang; Ting Wei; Zhiqin Cao; Qingyang Gu; Zhuang Liu; Rui Peng (Chemical Engineering Journal, 2023)

Patternable thermal conductive interface materials enabled by vitrimeric phase change materials - Li-Mei Peng; Zhao Xu; Jie Yang; Lu Bai; Rui-Ying Bao; Ming-Bo Yang; Wei Yang (Chemical Engineering Journal, 2023)

Coexistence of microplastics alters the inhibitory effect of antibiotics on sludge anaerobic digestion - Yinping Xiang; Weiping Xiong; Zhaohui Yang; Rui Xu; Yanru Zhang; Mengru Wu; Yuhang Ye; Haihao Peng; Jing Tong; Dongbo Wang (Chemical Engineering Journal, 2023)

Enhanced nitrogen removal in partial nitrification-anammox (PNA) suspended sludge system for real municipal wastewater treatment at extremely low carbon to nitrogen ratio - Hanbin Wang; Qiongpeng Dan; Rui Du; Jiapeng Li; Shuying Wang; Xiyao Li; Qiong Zhang; Yongzhen Peng (Chemical Engineering Journal, 2023)

Lattice doping of Zn boosts oxygen vacancies in Co3O4 Nanocages: Improving persulfate activation via forming Surface-Activated complex - Mei-Mei Wang; Li-Juan Liu; Jia-Rui Xi; Ying Ding; Peng-Xi Liu; Liang Mao; Bing-Jie Ni; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Rapid, selective, and room temperature dissolution of crystalline xylan by a hydrotrope - Qiaoling Liu; Rui Tian; Ziwen Lv; Yuying Wu; Baozhong Lv; Xiang Hao; Zhimin Xue; Feng Peng (Carbohydrate Polymers, 2023)

Ulva prolifera polysaccharide enhances the root colonisation by Bacillus amyloliquefaciens strain Cas02 - Depeng Chu; Xiaoqiang Wang; Jiajun Fan; Lijuan Peng; Jinchang Liang; Yanfen Zheng; Rui Wang; Xiangwei You; Changliang Jing; James Clark; Yiqiang Li; Yuan Yuan (Carbohydrate Polymers, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Plant-associated Microbe System in Treatment of Heavy Metals–contaminated Soil: Mechanisms and Applications - Zhiming Ren; Rui Cheng; Peng Chen; Yuanyuan Xue; Hong Xu; Yao Yin; Guangtuan Huang; Wei Zhang; Lehua Zhang (Water, Air, & Soil Pollution, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Leaching and characterization studies of heavy metals in contaminated soil using sequenced reagents of oxalic acid, citric acid, and a copolymer of maleic and acrylic acid instead of ethylenediaminetetraacetic acid - Eric Tindanzor; Zhaohui Guo; Tianshuang Li; Rui Xu; Xiyuan Xiao; Chi Peng (Environmental Science and Pollution Research, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

NLOS signal detection and correction for smartphone using convolutional neural network and variational mode decomposition in urban environment - Qi Liu; Chengfa Gao; Rui Shang; Zihan Peng; Ruicheng Zhang; Lu Gan; Wang Gao (GPS Solutions, 2023)